UNDANG-UNDANG PERKAWINAN DAN MARGINALISASI PEREMPUAN (Studi Kritis Terhadap Undang-undang Perkawinan No.1 Tahun 1974) - Nur Fadhilah, S.HI, M. Abdul Hamid, MA, (EGALITA, 2006)
Gender differences which generats gender role do not need to be refused as long as they do not cause undesirable impacts. However, the problem is that gender role creates unequality structures in particular aspects such as can be found in Marital Laws. Some sections of Marital laws are considered gender bias for women. For instance, section 31Â  verse 3 and section 4 are categorized as irrelevant sections to build gender as well as human rights equality which been recommended by CEDAW convention (Convention on the Elimination of Discrimination Againts Women) and Act no 7/1984. Therefore, these efforts should be taken to establish the Act or the regulation based on gender perspective to achieve equality and justice for both sexes (men and women) in all aspects particularly in a family relationship.